Optimization model in microalgae based biodiesel supply chain: A case study in the Philippines - Manalac, Aristotle J. (Animo Repository, 2016)
Microalgae biodiesel has gained significant support from the research community as a potential source of renewable energy due to its high productivity, flexibility, and wide range of by-products that improves its profitability. The Philippines is a good candidate for algal-based biodiesel production since it has abundant resources and tropical climate that can support its production. However, due to the archipelagic nature of the Philippines, The location of production site and target market should be considered carefully since it will have direct impact to the final cost of the biodiesel product and its carbon footprint due to transportation. Land and sea transportation routes are available to deliver the product to its consumers. This paper focus on the distribution system from production site to city local oil depot's scattered throughout the Philippines. A simple fictional case study is presented where distances used are in the same scale as the transportation routes possible in the Philippines. Carbon dioxide (CO2) emission and cost are the main criteria in judging the viability of the pathways from production sites to oil depots. Multi-criteria desirability function by Derringer and Suich is used to determine the aggregate desirability from the two criteria. Priority factors in the desirability function were varied in two case studies where cost is prioritized over emissions and vise versa. The model has demonstrated good sensitivity to the change of desirability factors. Land transportation is favored for cost effectiveness while sea transportation is favored in terms of CO2 emissions. The results of the study could be further improved by using actual data and obtaining priority factors from AHP or ANP to capture the priorities of the stake holders. © 2015 IEEE.